GARAP KARAWITAN DALAM KESENIAN LEBON DI SANGGAR JEMBAR MUSTIKA DESA SELASARI KECAMATAN PARIGI KABUPATEN PANGANDARAN - Rian Teguh Yogaswara, - (2020)
The research "Working on Karawitan in Lebon Art at Sanggar Jembar Mustika, Selasari Village, Parigi District, Pangandaran Regency", aims to describe the efforts to develop karawitan musical ideas, the process of implementing karawitan musical ideas and the results of the realization of karawitan musical ideas. The background to the problem has its own concept of working on karawitan in the art of lebon. The method used is descriptive analysis through qualitative paradigm. Data collection techniques in observation, used namely interviews, documentation and literature study. All data collected was processed and analyzed through data reduction, presentation, verification and conclusion. The findings of the results about the development of Karawitan musical ideas are the concept of work, determination of waditra, determination of musical arrangements. The process of implementing karawitan musical ideas in the art of lebon is the process of working on music and the process of practicing. The embodiment of Karawitan musical ideas in the art of lebon can be seen in the structure of the presentation, namely through the bubuka, content and closing stages